Meaning and Dentistry: Erasmus+ Disciplinary and Project Culture - Karapetjana, Indra; Rozina, Gunta; Sarmento, Clara (E- Revista de Estudos Interculturais, 2021)
The article reports on the multicultural cooperation experience of three higher education institutions from the Netherlands, Latvia and Portugal involved in the Erasmus+ project “Transversal Skills in Dentistry: Content and Language Integrated Approach” funded by the European Commission. Delineating the concept of culture, the article aims at discussing the project culture and the disciplinary culture, namely, dentistry as a hard discipline and linguistics as a soft discipline within the context of the Erasmus+ project. Although disciplinary differences should be taken into account when working on project outcomes, the methods applied profitably exist simultaneously. Successful creation of project culture, which was established at the outset by careful selection of the profile and background of participating organizations, allowed the consortium to agree on the roles and tasks of each organization involved in the project. The level of networking, cooperation and commitment of each partner in consortium to the fulfilment of the tasks in the project resulted in a high assessment of the project by the State Education Development Agency of Latvia. Despite the taken-on challenges of the cultures when developing the project outcomes, the participating organization sestablished and ran a cohesive consortium with active involvement of all partners and with the common goals achieved.